Implementation of Augmented Reality as an Interactive Medium for Firearms Education - Muhammad Nazar Darman; Yuli Asriningtias (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Augmented Reality (AR) has been utilized as an interactive educational tool to support safer and more effective learning about various firearms. The application was created with Unity3D and C#, and its functionality was evaluated through black box testing. Findings show that the application operates successfully on targeted devices, though some performance issues were observed, including extended loading times and occasional lag during navigation. AR visual and interactive features enable users to explore firearm components and operational procedures without exposure to real-world risks, as the use of physical firearms is not required. The inclusion of offline access further enables users to engage with the learning materials at their convenience. AR demonstrates considerable promise for improving the quality of firearm training and may be further adopted in technical instruction, military education, and the broader development of digital learning environments.